A new method for underwater archaeological surveying using sensors and unmanned platforms. Issue 23 (2016) - Ødegård, Øyvind; Sørensen, Asgeir J.; Hansen, Roy E.; Ludvigsen, Martin
Abstract: As most of the world's oceans are inaccessible to diving archaeologists, we must rely on advanced underwater technology and marine robotics to explore, map and investigate ship wrecks in these areas. New sensors and unmanned sensor platforms represent huge potentials for archaeological applications, but require a scrutinous look at how established archaeological methods and approaches must be adapted or rejected to optimize the results. Surveys done on a disintegrated wreck site with acoustic sensors like side scan sonar and synthetic aperture sonar, and optical sensors like stereo cameras, video and underwater hyperspectral imager, are compiled to serve as a case study to demonstrate the method. Challenges regarding guidance, navigation and control are discussed.